Manipulatives in Learning Fraction for Improving First-Year Elementary Students’ Understanding - Asoy, Ela; Boston, Edmarie; Madagmit, Ivy Mae; Bacatan, Jovenil (Universitas Pendidikan Indonesia (UPI), 2022)
This study was led to decide the effect of utilizing manipulatives in learning fraction. The examination demonstrated the effects of those manipulatives on learning fraction. The information was gathered from the sum number of 62 respondents, 31 students from the experimental group and 31 students from the control group, with the guide of the approved and validated test questionnaire. Information was investigated and translated utilizing the Average Weighted Mean and T-test as statistical tools. A pre-test and post-test were utilized to decide the results of utilizing manipulatives in the learning area. Data demonstrated that there was a significant difference in the utilization of Manipulatives for Learning Fraction among first-year elementary students. Some recommendations were also included in this study.